THE ROLE OF SELF CONCEPT TO ENCOURAGE IPHONE USERS’ LOYALTY - Nurkholish Majid; Nuruni Ika K.W; Nanik Hariyana (Politeknik Negeri Bengkalis, 2021)
Product and brand competition reach the smartphone industries by emphasizing satisfaction and loyalty to the brand. Iphone as a one of prestigious brand has a intense relationship with the consumer's image on themselves, which is known as the self-concept and then can be able to provide consumer loyalty to the brand. The purpose of this research is to explain empirically about 1) The effect of actual and ideal self-concept on the loyalty of iPhone users. The research sample was 100. The sample was taken using a non-probability sampling method with a purposive sampling technique. The selected respondents are Iphone users in Malang City who make personal purchasing decisions with a minimum of one year of use. Hypothesis testing was carried out using Partial Least Square (PLS) analysis. The results are actual and ideal self-concept provide the loyalty of iPhone users in the city of Malang. The actual and ideal self-concepts have a positive and significant influence on the loyalty of iPhone users.Product and brand competition reach the smartphone industries by emphasizing satisfaction and loyalty to the brand. Iphone as a one of prestigious brand has a intense relationship with the consumer's image on themselves, which is known as the self-concept and then can be able to provide consumer loyalty to the brand. The purpose of this research is to explain empirically about 1) The effect of actual and ideal self-concept on the loyalty of iPhone users. The research sample was 100. The sample was taken using a non-probability sampling method with a purposive sampling technique. The selected respondents are Iphone users in Malang City who make personal purchasing decisions with a minimum of one year of use. Hypothesis testing was carried out using Partial Least Square (PLS) analysis. The results are actual and ideal self-concept provide the loyalty of iPhone users in the city of Malang. The actual and ideal self-concepts have a positive and significant influence on the loyalty of iPhone users.